Effect of organic solvents on solvatochromic, fluorescence, and electrochemical properties of synthesized thiazolylcoumarin derivatives. (8th April 2021) - Bahadur, Ali; Iqbal, Shahid; Ujan, Rabail; Channar, Pervaiz Ali; AL‐Anazy, Murefah Mana; Saeed, Aamer; Mahmood, Qaiser; Shoaib, Muhammad; Shah, Mazloom; Arshad, Ifzan; Shabir, Ghulam; Saifullah, Muhammad; et al.
Abstract: In this present investigation, thiazolylcoumarin derivatives (5a –5k ) were synthesized from thiosemicarbazide, ethyl acetoacetate, and naphthaldehyde through a multistep route. The formation of thiazolylcoumarin derivatives with bioactive scaffolds was confirmed through nuclear magnetic resonance spectroscopy. A solvatochromic study of synthesized thiazolylcoumarin derivatives was carried out using ultraviolet–visible methods for dimethylformamide (DMF), ethyl acetate, and ethanol solvents. The redox behaviour of as‐synthesized thiazolylcoumarin derivatives (5a –5k ) was examined in dimethyl sulphoxide by conducting an electrochemical study. Fluorescence properties of thiazolylcoumarin derivatives were studied in DMF, ethanol, and ethyl acetate to visualize the solvent effect on the emitting ability of thiazolylcoumarin derivatives. Abstract : In this present investigation, novel thiazolylcoumarins were synthesized by a multistep route. Thiazolylcoumarins showed the solvatochromic effect in fluorescence and absorbance.